MENGKONSTRUK TOLERANSI MELALUI PENDIDIKAN WASATHIYA DI YAYASAN MASJID AL FALAH SURABAYA - Imam Syafi'i; Fathur Rofi'i (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2023)
This research aims to determine the construct of tolerance through wasathiya education at the Al Falah Mosque Foundation, Surabaya. The method used is descriptive qualitative with data collection techniques through observation, interviews and documentation. Meanwhile, the researcher used the Miles and Huberman analysis model for the data analysis technique. The research results show that wasathiya education at the Al Falah Mosque Foundation is in accordance with the teachings of the Qur'an and the Sunnah of the Prophet Muhammad which are limited by basic principles with the measuring instrument of the Pillars of Faith, Ahlus Sunnah wal Jama'ah with a broad understanding. The form of tolerance at the al Falah Mosque Foundation is: Firstly, all Community Organizations can become speakers, pentausiahs and preachers as long as they are in accordance with the goals of the al Falah Foundation which is to enlighten, soothe and unite the people. The second identity of the Al Falah Mosque Foundation is for all groups, groups, governments. Third, the implementation of worship is more dominant towards Muhammadiyah teachings but does not claim to belong to mass organizations and the government. The four congregations were given leeway in expressing their opinions.